The Impact of Cognitive Style-based Learning Models on Students' Problem-Solving Abilities - Sutrisno, Sutrisno; Rahayuningsih, Dwi; Purwati, Heni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
Every student must possess problem-solving abilities. Solving students' problems is varied; several factors influence the difference between cognitive styles and learning models. This study aimed to determine differences in problem-solving abilities based on students' cognitive styles in the Concept Attention (CA) and Group Investigation (GI) learning model. This study was a quantitative study with the tenth-grade students of SMA Negeri 16 Semarang as the 2018/2019 academic year population. The sample was selected using cluster random sampling. The research data had been collected through documentation and tests and then were analyzed using nonparametric tests, specifically the Hildebrand test, since the data were not normally distributed. The results showed that students with Field Independent (FI) cognitive style's problem-solving ability were better than students with Field Dependent (FD) cognitive style, either in general, CA, or GI learning models. The CA learning model produced better problem-solving abilities than the GI learning model, both in general and in terms of the type of students’ cognitive style.